2021
DOI: 10.1002/ctm2.467
|View full text |Cite
|
Sign up to set email alerts
|

Functional inhibition of lactate dehydrogenase suppresses pancreatic adenocarcinoma progression

Abstract: Background Pancreatic adenocarcinoma (PAAD) a highly lethal malignancy. The current use of clinical parameters may not accurately predict the clinical outcome, which further renders the unsatisfactory therapeutic outcome. Methods In this study, we retrospectively analyzed the clinical‐pathological characteristics and prognosis of 253 PAAD patients. Univariate, multivariate, and Kaplan‐Meier survival analyses were conducted to assess risk factors and clinical outcomes. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 69 publications
3
29
0
Order By: Relevance
“…The hypoxia-related risk signature consists of eight hypoxia-related genes, including LDHA, DCN, PGK1, PFKP, FBP1, LOX, ENO3, and CXCR4. LDHA is an enzyme that catalyzes the mutual conversion of pyruvate and lactic acid, as well as promotes invasion, metastasis, nest loss, and apoptosis resistance in various cancers ( Cheng et al, 2021 ; Crowley et al, 2021 ; Gupta et al, 2021 ). Multiple studies have suggested that DCN can suppress lung cancer progression by blocking receptor tyrosine kinases ( Horvath et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hypoxia-related risk signature consists of eight hypoxia-related genes, including LDHA, DCN, PGK1, PFKP, FBP1, LOX, ENO3, and CXCR4. LDHA is an enzyme that catalyzes the mutual conversion of pyruvate and lactic acid, as well as promotes invasion, metastasis, nest loss, and apoptosis resistance in various cancers ( Cheng et al, 2021 ; Crowley et al, 2021 ; Gupta et al, 2021 ). Multiple studies have suggested that DCN can suppress lung cancer progression by blocking receptor tyrosine kinases ( Horvath et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alphaenolase (EN O 1), one of the three enolase isozymes, participates in the adhesion, invasion, and metastasis of PDAC by controlling integrin expression (Principe et al, 2017). Lactate dehydrogenase A (LDHA) is a cytoplasmic enzyme, and overexpression of LDHA promotes PDAC proliferation and invasion in vitro by regulating phosphorylation of AMPK and mTOR (Cheng et al, 2021). Inhibition of LDHA has no significant toxic effects on normal tissues; therefore, LDHA may serve as a promising target for tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, phosphorylation on Ser226 in GLUT1 was identified as a key event for the enhanced cell surface localization of GLUT1 and for the regulation of glucose transport (55). A sustained elevated glycolytic flux in PDAC is markedly connected with an increased expression of rate-limiting glycolytic enzymes like phosphofructokinase 1 and lactate dehydrogenase A (LDHA) (56)(57)(58), and there is also evidence of glycolytic enzymes regulating the epithelial-mesenchymal transition (EMT) in PC cells, inducing PC cell invasion and metastasis as well as promoting tumor angiogenesis (59)(60)(61)(62)(63). The Raf/MEK/extracellular signal-regulated kinase (ERK) signaling pathway activated by oncogenic KRAS together with hypoxic conditions known to be present in PDAC increase glucose uptake and the expression of glycolytic enzymes, which then leads to the establishment of an acidic microenvironment and the promotion of tumorigenesis (57,64).…”
Section: Glucose Lactate and The Metabolic Collaboration In The Tumor...mentioning
confidence: 99%